Dimensionen der Altersarmut in Deutschland – Ein Erklärungsmodell basierend auf dem Befähigungsansatz nach Martha C. Nussbaum - Reinecke, Frank (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2012)
In Germany, an increasing number of elderly people live in a state of old-age poverty or are at risk of falling into poverty. The explanation of the dimensions of old-age poverty in Germany is focus of this thesis. On the basis of the justice theory of Martha C. Nussbaum, the Capability Approach, the global dimensions of old-age poverty can be investigated. The reality of old-age poverty in Germany is defined by Christian social ethics and global poverty dimensions are set in a nationwide context. From the basic facts obtained about old-age poverty in Germany an overall definition of the term ‘old-age poverty’ can be made. This draft definition will subject to the challenge of an interdisciplinary scientific discussion. The results of the research enable society, state, social work and others to take action to reduce, avoid and overcome old-age poverty.

Eine steigende Zahl älterer Menschen lebt in Deutschland im Zustand der Altersarmut oder ist von Altersarmut bedroht. Die Klärung von Dimensionen der Altersarmut in Deutschland steht im Zentrum der Dissertation. Anhand der Gerechtigkeitstheorie von Martha C. Nussbaum, dem Capability Approach, lassen sich globale Dimensionen von (Alters-)Armut ermitteln. Die Altersarmutswirklichkeit in Deutschland wird durch die christliche Sozialethik beschrieben und die globalen Armutsdimensionen werden in den bundesdeutschen Armutskontext gesetzt. Aus den ermittelten Grundlagen zur Altersarmut in Deutschland ergibt sich eine erste ganzheitliche Definition des Begriffs ‚Altersarmut’. Dieser Begriffsentwurf soll einer wissenschaftlichen, interdisziplinären Diskussion ausgesetzt werden. Die Ergebnisse der Forschungsarbeit ermöglichen Handlungsempfehlungen für Gesellschaft, Staat, Soziale Arbeit und die Menschen, die zum Abbau, zur Vermeidung und zur Bewältigung von Altersarmutszuständen beitragen können.
Dimensions of old-age poverty in Germany - a model of explanation based on the capability approach of Martha C. Nussbaum
Keywords: Altersarmut; 300 Sozialwissenschaften